Chemotherapeutic potential of novel non-toxic nucleoside analogues on EAC ascitic tumour cells. (2nd January 2019) - Barua, Atish; Choudhury, Pritha; Maity, Joy Krishna; Mandal, Sukhendu Bikash; Mandal, Suvra; Saha, Prosenjit
Abstract: Therapeutic efficacy of nucleoside analogues (NAs) like Gemcitabine, 5-fluorouracil in cancer treatment is already well established. Most of the known NAs are highly toxic to normal cells due to its non-specific action; thus searching for non-toxic NAs are still going on. For that purpose we have synthesised nine different NAs by alteration of their structural and functional groups. The aim of present study is to investigate the therapeutic potential of NAs against mice bearing breast adenocarcinoma cells at IC50 dose for 10 days treatment schedule. Results of the present study showed that, among the seven nucleoside analogues, NA-7 and NA-9 showed maximum therapeutic efficacy in controlling cancer cells by inhibiting cell proliferation and inducing apoptosis without any adverse effects to normal host cells. Additionally, NAs significantly decreased the tumour burden and enhanced survivability of host through generation of reactive oxygen species in tumour cells. These ultimately led to DNA damage, depolarisation of mitochondrial membrane potential and apoptosis in tumour cells. To find out the molecular mechanisms, we showed that administration of NA-7 and NA-9, down- regulating the expression of Bcl-2, cyclin D1, C-myc, P-21 and up-regulating the expression of P-53, Cyt-c, Bax, caspase-3 and caspase-9. The results suggest that NA-7 and NA-9 exhibits significant antitumor activity than 5-fluorouracil by modulating the cell cycle checkpoints and inducing apoptosis in Ehrlich ascites carcinoma (EAC)-bearing mice. Additionally, NA-7 and NA-9 did not show any clastogenic effect on bone marrow cells at sub-lethal dose. Thus, the present study clearly suggested therapeutic benefit of NAs by augmenting anticancer efficacy and diminishing toxicity to the host.